2019
DOI: 10.1038/s41467-019-09751-4
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the gap between transition metal- and bio-catalysis via aqueous micellar catalysis

Abstract: Previous studies have shown that aqueous solutions of designer surfactants enable a wide variety of valuable transformations in synthetic organic chemistry. Since reactions take place within the inner hydrophobic cores of these tailor-made nanoreactors, and products made therein are in dynamic exchange between micelles through the water, opportunities exist to use enzymes to effect secondary processes. Herein we report that ketone-containing products, formed via initial transition metal-catalyzed reactions bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
159
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 186 publications
(163 citation statements)
references
References 49 publications
2
159
0
2
Order By: Relevance
“…[200][201][202][203] A recent important publication by Lipshutz and coworkers has shown that the formation of micelles in the reaction medium can facilitate the combination of chemo-and bio-catalysis in a single reactor as the substrates, products and catalysts partition into the different compartments. 204 For an extensive review of the recent literature on biocatalytic cascade reactions see Kroutil and coworkers. 205…”
Section: Integration: Biocatalytic and Chemoenzymatic Cascade Processesmentioning
confidence: 99%
“…[200][201][202][203] A recent important publication by Lipshutz and coworkers has shown that the formation of micelles in the reaction medium can facilitate the combination of chemo-and bio-catalysis in a single reactor as the substrates, products and catalysts partition into the different compartments. 204 For an extensive review of the recent literature on biocatalytic cascade reactions see Kroutil and coworkers. 205…”
Section: Integration: Biocatalytic and Chemoenzymatic Cascade Processesmentioning
confidence: 99%
“…Designer surfactants based on aqueous micellar solutions have recently been demonstrated as innovative reaction media for chemo‐enzymatic cascades . While they were initially designed for synthetic chemistry in water, Lipshutz et al.…”
Section: Chemoenzymatic Synthetic Cascadesmentioning
confidence: 99%
“…Surfactants are available in large quantities permitting immediate scale up, the micelle core is typically dynamic (liquid at rt) providing reasonable diffusion constants, and the core size is on the order of few nanometers, increasing the interfacial area with the continuous phase. Micelle catalysis is a highly active field and has recently been used for Pd-catalyzed Sonogashira coupling [ 86 ], Rh-catalyzed C-H arylation [ 87 ], and for one-pot cascade catalysis of metal-complex chemo- and enzyme bioconversions under aqueous conditions [ 88 ], amongst others. Modifications to the chemical structure of small molecular weight surfactant are however limited, as these alter the self-assembly behavior and physicochemical properties.…”
Section: Block Copolymer Micellesmentioning
confidence: 99%